2012
DOI: 10.1016/j.bmcl.2012.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pacidamycin analogues via an Ugi-multicomponent reaction

Abstract: The second-generation synthesis of 3'-hydroxypacidamycin D (2) has been accomplished via an Ugi-four component reaction at a late stage of the synthesis. This approach provided ready access to a range of analogues including diastereomers of the diaminobutylic acid residue and hybrid-type analogues of mureidomycins. Biological evaluations of these analogues indicated that the stereochemistry at the diaminobutylic acid residue has a crucial impact on both the MraY biochemical inhibition and whole-cell anti-bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78. The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78. The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…As such, analogues 7–17 , retaining the DABA unit (due to the previously established importance of the N - and β-methyl moieties for activity283233) but possessing a variety of functionalities in place of the m -Tyr moiety, were proposed (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Fer et al have also synthesised a series of triazole-containing analogues of the caprazamycins, which show IC50 values of 100-1000 µM against B. subtilis MraY, and show antibacterial activity against Staphylococcus aureus [31]. total synthesis of pacidamycin D [32], and have used the synthetic route to investigate structure-activity relationships in he N-terminal dipeptide chain [33], shown previously to be important for biological activity in the mureidomycin series [34]. The stereochemistry of the 2,3-diaminobutyric acid unit at C-2 was found to be important for both MraY inhibition and antibacterial activity, and meta-tyrosine was 180-fold more active for MraY inhibition than Ltyrosine in the N-terminal dipeptide [33].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%
“…total synthesis of pacidamycin D [32], and have used the synthetic route to investigate structure-activity relationships in he N-terminal dipeptide chain [33], shown previously to be important for biological activity in the mureidomycin series [34]. The stereochemistry of the 2,3-diaminobutyric acid unit at C-2 was found to be important for both MraY inhibition and antibacterial activity, and meta-tyrosine was 180-fold more active for MraY inhibition than Ltyrosine in the N-terminal dipeptide [33]. Two new series of peptidyl-uridines whose structures are based upon mureidomycin A and tunicamycin have been synthesised as inhibitors of C. jejuni PglC, and selected compounds show IC50 values in the range 40-250 µM [35].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%
“…More recently, the Ugi reaction was applied at a late stage of the synthesis of 3′-hydroxypacidamycin D (Scheme 22) [89]. The urea dipeptide 55 , 2,4-dimethoxybenzylamine, the protected ( S )-2-(methylamino)propanal, and isonitrile 56 were simply combined in ethanol at ambient temperature for 48 h. The expected compound 57 and its epimer were obtained in reasonable yields, and were separated by column chromatography.…”
Section: Reviewmentioning
confidence: 99%